Comprehensive Insights into Historical Events: Visual and Verbal Associations of Students in Ukraine, Israel, and Poland - Davidovitch, Nitza; Gerkerova, Aleksandra; Thomas, Katarzyna (Journal of Education Culture and Society, 2025)
Aim. This research aims to examine, through a questionnaire using visual and verbal free associations, whether the Holocaust, the war in Ukraine, and the war in Israel are perceived as distinct, unique events or if they merge with other military conflicts in students’ perceptions worldwide.Methods. A total of 82 students from Ukraine, Israel, and Poland participated in this study. The methodology combined visual and verbal free association tasks, where students responded to a series of photographs depicting the Holocaust, the war in Ukraine, and other conflicts. Demographic data such as academic discipline and cultural background were collected to analyse their influence on students’ perceptions.Results. The Holocaust is largely perceived as a unique and unparalleled historical event, particularly by students from Israel and Poland, who associate it with themes such as inhumanity, grief, and fear. In contrast, some students view more contemporary conflicts, such as the war in Ukraine and the war in Israel, through a comparative lens, often linking them to broader global conflicts. Ukrainian students tend to see the war in Ukraine as a unique event, while Israeli students show a similar perspective regarding the war in Israel, associating it with themes of chaos, struggle, and survival.Conclusions. This study highlights the significance of the Holocaust in shaping collective historical memory and emphasises the role of educational and cultural backgrounds in these perceptions. The findings underscore the importance of educational strategies that maintain the distinct historical significance of the Holocaust while fostering empathy and critical thinking, offering valuable insights for educators and policymakers.